Early in-hospital discontinuation of aspirin following coronary stent implantation in patients with indication for direct oral anticoagulation. (3rd October 2022) - Von Stein, P; Seitz, L; Wienemann, H; Hohmann, C; Baar, T; Baldus, S; Halbach, M
Abstract: Background and purpose: 5–10% of patients undergoing percutaneous coronary intervention (PCI) have an indication for oral anticoagulation (OAC). Triple therapy, i.e. anticoagulation plus dual antiplatelet therapy, is associated with a high bleeding rate. Discontinuation of aspirin while continuing direct OAC (DOAC) and a P2Y12 inhibitor (so-called dual therapy) after PCI, was investigated in four randomized trials demonstrating a reduction in bleeding without significant differences in ischemic events. Since randomization was performed several days after the index PCI, these trials allowed for a short period of triple therapy. Whether exclusive procedural application of aspirin and early discontinuation of aspirin at the first postprocedural day is safe, is unknown and was the scope of this work. Methods and results: We retrospectively analysed 3613 patients (4564 PCIs) treated from 2017 to 2020 at our centre. 871 (24.1%) patients (1059 PCIs, 23.2%) had an indication for OAC. In 284 PCIs with stenting, patients received DOAC (71.8% Rivaroxaban, 25.7% Apixaban, 1.8% Dabigatran, 0.7% Edoxaban) + P2Y12 inhibitor (100% clopidogrel) + aspirin only at the day of procedure (group 1). In 52 PCIs with stenting, patients received DOAC (59.6% Rivaroxaban, 34.6% Apixaban, 1.9% Dabigatran, 3.9% Edoxaban) + P2Y12 inhibitor (100% clopidogrel) + 100 mg aspirin/d at ≥1 postprocedural day (group 2). Based on our local patient database, we analysed the rate of ischemic events (myocardial infarction, stent thrombosis, stroke/transient ischemic attack (TIA), pulmonary/systemic embolism (PE/SE), deep vein thrombosis) as well as major and minor bleeding according to the Thrombolysis in Myocardial Infarction (TIMI) criteria during hospitalisation. Data are presented as mean±standard deviation or median (range). Baseline characteristics were similar (group 1 vs. group 2: 74.3% vs. 73.1% male, age 75.9±8.5 vs. 74.3±9.3 years, atrial fibrillation 91.2% vs. 88.5%), except previous PE (3.5% vs. 11.5%; p=0.024), type of preprocedural DOAC (Rivaroxaban 52.5% vs. 34.6%; p=0.023) and creatinine clearance (62.4±19.7 vs. 68.9±20.3 ml/min; p=0.029). Median duration of postprocedural hospitalisation was 1 day for both groups (0–20 days vs. 1–21 days). In both groups, one TIA occurred (p=0.292), there were no other ischemic events. 36 (12.7%) bleeding events occurred in group 1 and 11 (21.2%) in group 2 (p=0.126). A subgroup analysis of cases being hospitalised for ≥2 postprocedural days (group 1: 87 cases, median 4 (2–20) days; group 2: 20 cases, median 2 (2–21) days) found no ischemic events and no difference regarding bleeding events (34.5% vs. 45.0%; p=0.443). Conclusions: Exclusive procedural application of aspirin and start of dual therapy at the first postprocedural day appears safe regarding ischemic events in a real-world population. Nearly ¼ of patients undergoing PCI had an indication for OAC, which is much more frequent than previously reported. Funding Acknowledgement: Type of funding sources: None.